Development of Canva-Based Digital Comics Integrated with Islamic Values to Improve Elementary Students’ Reading Interest in Fable Learning - Salwangi, Salwangi; Nawas, Muhammad Zuhri Abu; Aswar, Nurul (State Islamic University of Palopo, 2025)
This study aimed to develop and evaluate a Canva-based digital comic integrated with Islamic values for improving elementary school students’ reading interest in fable learning. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of the study were 30 third-grade students of SD Negeri 24 Temmalebba Kota Palopo. Data were collected through observations, interviews, questionnaires, and reading interest tests. The data were analyzed using descriptive qualitative and quantitative techniques. The results of the needs analysis revealed that students’ reading interest was still low and the learning process was dominated by conventional textbook-based instruction with limited visual media. Based on these findings, a Canva-based digital comic was designed and developed by integrating Islamic values such as honesty, responsibility, and cooperation into fable stories. The validation results showed that the developed media achieved a valid category in terms of media, material, and language aspects, with an average validity score of 83.87%. The practicality test indicated that the media was categorized as very practical, with teacher and student response scores of 92% and 88%, respectively. Furthermore, the effectiveness test demonstrated an increase in students’ reading interest, as indicated by the improvement of the average score from 62 in the pretest to 84 in the posttest, with a gain score of 0.58 in the moderate category. The findings indicate that the Canva-based digital comic integrated with Islamic values is valid, practical, and effective in improving students’ reading interest and supporting character education in elementary schools.